Konsep Pendidikan Ki Hajar Dewantara dan Relevansinya dengan Pendidikan Madrasah Ibtidaiyah - Firmansyah, Edwin; Nasucha, Zubaedah; Muzfirah, Suci (Al-Azkiya: Jurnal Pendidikan MI/SD, 2021)
This study focuses on the concept of Ki Hajar Dewantara's thinking for its relevance to education in Mi at this time. MI. Practically, this research is expected to provide clarity on the concept of education according to Ki Hajar Dewantara, thus providing a bright spot on its relevance to education at MI today, and can contribute to finding solutions to the problems that are being faced by the Indonesian nation. This research is a qualitative research with the type of library research, namely exploring Ki Hajar Dewantara's thoughts on education. The data collection technique that the author uses is to collect books, journals and others related to the subject matter. The data that has been collected was analyzed using descriptive methods, namely research methods that seek to reveal the facts of an event, object, activity, and process. The results of this study indicate that Ki Hajar's educational concept is still relevant today. Judging from his thoughts in accordance with the concepts that are still being implemented, namely education and teaching which is a deliberate effort to liberate the outer and inner aspects of humans.